O lúdico no currículo da educação infantil: debates e proposições contemporâneos - Câmera, Rosângela Silva Neto (2012)
Recent years have been marked in our country by a vigorous critical reflection on the construction of a democratic education, whose curricula and teaching practice which takes into account the heterogeneity of cultures and social classes and promoting the development of children in the fullness of the multiple expressions playful. This study aims to argue and understand the propositions and the theoretical debates about the presence of play in the curriculum of early childhood education, and develop relevant and pertinent indications about the experience of play in the systematic education of children. In this context, this paper's main theoretical studies of Huizinga (1993),Kramer (1989), Kshimoto (1994), Luckesi (2000), Macedo (2002), Morin (2000),Piaget (1990), Porto ( 2002), Vygotsky (1998), among others. The method chosen was the literature search, it is a method that references theoretical as well as establishing systematic relations between concepts, encouraging discussion, explanation and relevance of systems of ideas discussed. The exercise methodology anchored in a semiological hermeneutics of the texts worked, without thereby prevent us to transcend the analytic sources of inspiration.